Comparison of the environmental, economic and energy performance of ETICS with ICB and with EPS - Silvestre, José D. (2015)
This study presents a comparison between ETICS (External Thermal Insulation Composite System) using two alternative materials, Insulation Cork Boards (ICB) and Expanded Polystyrene (EPS), for a 50-year horizon. The environmental balance is based on “cradle to grave” (C2G) Life Cycle Assessment (LCA) studies, and focused on the car- bon footprint and the consumption of renewable and non-renewable primary energy of these materials. The energy balance considers the main thermal insulating characteristics of these products, including the improvements on the energy performance of the buildings envelope after its installation for renovation and the corresponding energy savings. The final balance between the environmental and energy performance includes the estimation, from C2G, of: the carbon saved and the consumption of renewable and non-renewable primary energy. The analysis of the results of this study shows that external wall alternatives of ETICS with ICB have an environmental advantage in terms of the categories “Global Warming Potential” (GWP) and consumption of non-renewable primary energy (PE-NRe), namely due to the production stage of ICB in comparison with EPS. Assessing the energy consumption needed to fulfil the heating and cooling needs of the interior space of a building for both solutions with the same thickness, the EPS solution requires lower energy consumption, due to its lower U-Value. The lower acquisition cost of this solution always results on a lower “Cradle to Cradle” (C2C) cost. Comparing two solutions with similar U-values but different thicknesses (the ICB boards with a bigger thickness due to the lower U-Value), the consumption of energy needed to fulfil the heating and cooling needs is almost the same, differing in the acquisition cost of the solutions and in the energy and resources necessary in the production of the materi- als. Due to high commercial cost of ICB, the EPS solution always presents a lower Net Present Value (NPV) of the economic and energy cost.